Orbital Surface Hopping from the Orbital Quantum-Classical Liouville Equation for Nonadiabatic Dynamics of Many-Electron Systems - Ma, Yong-Tao; Bi, Rui-Hao; Dou, Wenjie (Journal of chemical theory and computation, 2025)
Accurate simulation of the many-electron nonadiabatic dynamics process at metal surfaces remains a significant challenge. In this work, we present an orbital surface hopping (OSH) algorithm rigorously derived from the orbital quantum-classical Liouville equation (o-QCLE) to address nonadiabatic dynamics in many-electron systems. This OSH algorithm is closely connected to the popular independent electron surface hopping (IESH) method, which has demonstrated remarkable success in addressing these nonadiabatic phenomena, except that electrons hop between orbitals. We compare the OSH approach with the IESH method and benchmark these two algorithms against the surface hopping method using a full configuration interaction (FCI) wave function. Our approach shows strong agreement with IESH and FCI-SH results for molecular orbital populations and kinetic energy relaxation, while also exhibiting high efficiency, thereby demonstrating the capability of the new OSH method to capture key aspects of many-electron nonadiabatic dynamics.